Does the benevolence value matter when social media burnout strikes?. (4th February 2021) - Han, Bo; Chou, Shih Yung; Chang, Tree
Social media burnout has become a new issue to many users. This study introduces a new model to test if a user's benevolence value can have a mediation effect when he/she experiences social media burnout. We recruited Facebook users from a student population at a US university to participate in a survey-based study. 290 valid and complete responses were received. The data analysis result shows that benevolence has a strong negative effect on a user's social media burnout perceptions such as ambivalence and emotional exhaustion, and can significantly positively influence the user's social media continuance. Our study is the first of its kind that integrates benevolence value into a user's post-adoption experience research. The newly proposed model can help social media research community to gain more insights on the roles a user's value plays in his/her perceptions and intentions in the post-adoption stage.